Investigation of trends in gut microbiome associated with colorectal cancer using machine learning - Yu, Chaoran; Zhou, Zhiyuan; Liu, Bin; Yao, Danhua; Huang, Yuhua; Wang, Pengfei; Li, Yousheng (Frontiers in Oncology, 2023)
Background The rapid growth of publications on the gut microbiome and colorectal cancer (CRC) makes it feasible for text mining and bibliometric analysis. Methods Publications were retrieved from the Web of Science. Bioinformatics analysis was performed, and a machine learning-based Latent Dirichlet Allocation (LDA) model was used to identify the subfield research topics. Results A total of 5,696 publications related to the gut microbiome and CRC were retrieved from the Web of Science Core Collection from 2000 to 2022. China and the USA were the most productive countries. The top 25 references, institutions, and authors with the strongest citation bursts were identified. Abstracts from all 5,696 publications were extracted for a text mining analysis that identified the top 50 topics in this field with increasing interest. The colitis animal model, expression of cytokines, microbiome sequencing and 16s, microbiome composition and dysbiosis, and cell growth inhibition were increasingly noticed during the last two years. The 50 most intensively investigated topics were identified and further categorized into four clusters, including “microbiome sequencing and tumor,” “microbiome compositions, interactions, and treatment,” “microbiome molecular features and mechanisms,” and “microbiome and metabolism.” Conclusion This bibliometric analysis explores the historical research tendencies in the gut microbiome and CRC and identifies specific topics of increasing interest. The developmental trajectory, along with the noticeable research topics characterized by this analysis, will contribute to the future direction of research in CRC and its clinical translation.